2005
DOI: 10.2174/1568008054064940
|View full text |Cite
|
Sign up to set email alerts
|

Drugs Affecting Biliary Lipid Secretion and Gallbladder Motility: Their Potential Role in Gallstone Treatment and Prevention

Abstract: Gallstone disease in the Western world has an estimated prevalence of 10-15% and more than 75% are cholesterol-enriched gallstones. Defective gallbladder motility has been identified as an important pathogenic factor for cholesterol gallstone disease. Various agents may enhance or impair postprandial gallbladder motility, and their effects on interdigestive gallbladder and intestinal motility should also be taken into account. Patients in high-risk situations for gallstone disease, and those chronically treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…One patient in our cohort received ursodeoxycholic acid because of gallstone‐related abdominal pain but developed cholecystitis 2 months after initiation of this therapy. With no prospective, randomized trials in somatostatin–analog patients, and with a reported high recurrence rate, ursodeoxycholic acid therapy needs to be investigated further and used only for patients with high operative risk [2, 6, 13, 14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One patient in our cohort received ursodeoxycholic acid because of gallstone‐related abdominal pain but developed cholecystitis 2 months after initiation of this therapy. With no prospective, randomized trials in somatostatin–analog patients, and with a reported high recurrence rate, ursodeoxycholic acid therapy needs to be investigated further and used only for patients with high operative risk [2, 6, 13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these analogs have become a cornerstone for the treatment of these patients. However, the treatment may have adverse effects as increased formation of cholesterol-rich crystals in the bile and suppression of cholecystokinin, which may impair gallbladder emptying and inhibit relaxation of sphincter oddi, lead to enhanced gallstone formation [2][3][4][5][6][7]. Although initial studies of somatostatin analogs indicated these effects, no long-term study has confirmed the clinical impact, and recommendations regarding gallbladder surgery in carcinoid patients have been vaguely based.…”
Section: Introductionmentioning
confidence: 99%
“…Motilin-analogue erythromycin, intravenous administration of a mixture of essential and non-essential amino acids, cholinomimetic drugs, such as bethanecol and prostigmine, stimulate gallbladder contraction (10,11). Likewise, intravenous injection of nonionic iodinated contrast media or ingestion of water or a dilute solution of contrast medium for various radiological examinations results in the contraction of the gallbladder (2)(3)(4)(5).…”
Section: Abstract: • Gallbladder • Ultrasound • Contrast Media • Magmentioning
confidence: 99%
“…Cholelithiasis is a worldwide disease and it remains to be one of the most common health problems leading to surgical intervention (1,2) . Cholelithiasisis is common with the incidence ranging from (10-20)% of the world population (3) ,the prevalence of cholelitheasis varies considerably within population; the highest known prevalence is among American Indians with up to (60-70) % in females (4) and (10)(11)(12)(13)(14)(15) % in white adults of developed countries (5) .Cholelithiasis is classified as either cholesterol stones (Cs), pigment stones (Ps), or mixed stones (Ms) (6) .These categories of gallstones can be identified according to their predominant chemical composition (7) . Two thirds of individuals with cholelithiasis is asymptomatic (8) .…”
Section: Introductionmentioning
confidence: 99%